Public and Elite Policy Preferences: Gay Marriage in Canada - Pettinicchio, David (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2010)
This paper explores the role of parties, interest groups and public opinion in the enactment of ‘controversial’ social policy particularly when the issue is salient with political elites, but not salient with the public. The author analyses party documents, interest group testimony, media statements and public opinion data. He finds that political elites in Canada facilitated the legalisation of gay marriage while anti-gay marriage politicians and interest groups were unable to reframe gay marriage so as to benefit their cause. While political elites engaged in an ongoing discourse, Canadians remained divided on same-sex marriage but also uninterested in the issue. This paper also discusses the key differences surrounding the legalization of same-sex marriage between the United States and Canada.